Railways communications propagation prediction over irregular terrain using longley-rice model - Prior, Pedro (2021)
This paper presents the evaluation results of the radio signal propagation prediction using Longley-Rice model in railways installed in rural areas with significant variation of propagation path and terrain profiles. The prediction results were compared with measurement acquired by installing several CW emitters along the railway and reception equipment installed on a rolling stock. In addition, the results were also compared with the prediction based on Okumura-Hata model. The obtained results prove Longley-Rice suitability for railways communication prediction on irregular terrain, achieving better results than the Okumura-Hata model.